2013
DOI: 10.1111/bph.12222
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and ligand bias at the μ‐opioid receptor

Abstract: In order to describe drug action at a GPCR, a full understanding of the pharmacological terms affinity, efficacy and potency is necessary. This is true whether comparing the ability of different agonists to produce a measurable response in a cell or tissue, or determining the relative ability of an agonist to activate a single receptor subtype and produce multiple responses. There is a great deal of interest in the μ-opioid receptor (MOP receptor) and the ligands that act at this GPCR not only because of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 93 publications
1
128
0
1
Order By: Relevance
“…Indeed, MOR has been shown to be capable of activating ERK1/2 in striatal neurons when stimulated by a different opioid agonist fentanyl in a manner dependent on GRK3/β-arrestin [41]. This example serves to reinforce the ligand dependent nature of opioid receptor signaling that is becoming an increasingly accepted model of GPCR signaling [43, 44]. Nevertheless, from the perspective of G protein mediated transmission downstream from MOR, Ras signaling to Akt-mTOR/GSK3β seems to be the dominant pathway regulated by NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MOR has been shown to be capable of activating ERK1/2 in striatal neurons when stimulated by a different opioid agonist fentanyl in a manner dependent on GRK3/β-arrestin [41]. This example serves to reinforce the ligand dependent nature of opioid receptor signaling that is becoming an increasingly accepted model of GPCR signaling [43, 44]. Nevertheless, from the perspective of G protein mediated transmission downstream from MOR, Ras signaling to Akt-mTOR/GSK3β seems to be the dominant pathway regulated by NF1.…”
Section: Discussionmentioning
confidence: 99%
“…An extension of this hypothesis regarding direct coupling of a GPCR to GaGPR is that a GPCR may couple to GaGPR in a ligand-dependent, conformationally-selective manner analogous to ligand-bias as described for GPCR coupling to Gabg and b-arrestin, offering substantial flexibility for systems to adapt and respond to extracellular stimuli (Fig. 2C) (Brink et al, 2000;Gesty-Palmer and Luttrell, 2011;Blattermann et al, 2012;Kenakin, 2012;Pradhan et al, 2012;Reiter et al, 2012;Rivero et al, 2012;Ahn et al, 2013;DeWire et al, 2013;Katritch et al, 2013;Kelly, 2013;Kenakin and Christopoulos, 2013;Wehbi et al, 2013;Wootten et al, 2013). One might imagine that receptor coupling to these three distinct transducer elements would regulate different signaling pathways and/or the strength and duration of generated signals and offer additional opportunities to expand upon the concept of pathway targeted drugs.…”
Section: Two Core Signaling Triadsmentioning
confidence: 99%
“…β-arrestin binding leads to receptor internalization and activation of a distinct group of signaling proteins such as extracellular signal-regulated kinase (ERK1/2), which is well characterized in adrenergic receptors compared to opioid receptors (Lefkowitz and Shenoy, 2005, Shenoy and Lefkowitz, 2005, Drake et al, 2008). Recent studies have shown that some MOPr agonists such as fentanyl and [D-Ala 2 , N-MePhe 4 , Gly-ol]-enkephalin (DAMGO) have high efficacy to recruit β-arrestin and activate of G proteins, whereas other opioids such as morphine are biased toward G protein signaling (McPherson et al, 2010, Molinari et al, 2010, Kelly, 2013, Thompson et al, 2014). …”
Section: Introductionmentioning
confidence: 99%